Strategi pembelajaran anak lamban belajar (slow learner) pada pembelajaran jarak jauh siswa sekolah dasar - Yasinta Nur Annisa; Sri Marmoh; Hadiyah Hadiyah (Universitas Sebelas Maret, 2023)
This study aims to describe the teachers strategy in dealing with Slow Learners for fifth grade students at SD Negeri 2 Ngringo. The method used in this research is qualitatitve method. This research was conducted at SD Negeri 2 Ngringo. The data in sthis study are the result of interviews with the fifth grade homeroom teacher of SD Negeri 2 Ngringo and 6 students, the results of observations of the learning process, and study documentation. Data collection techniques using interviews, observation, and documentation. The data analysis technique in research is interactive analysis with the stages of data collection, data, reduction, data presentation, and drawing conclusions. The triangulation technique uses data sources. The results of this study reveal a special strategy applied by classroom teachers, namely using an individual of student-centered learning approach and a remedial approach. This individual approach is carried out with special meetings given by the teacher to those who are indicated to have learning delays (Slow Learners). So, by using this approach it is hoped that the teachers will be able to ensure that students are able to understand and process material optimally in the distant learning process. In addition, studentlearning development can also be monitored specicically for teachers to carry out the process of assessing learning development in order to achieve optimal learning goals for Slow Learners.Kata kunci: distance learning,strategy,slow learners